En-Knap Dance Company Recent Review - Roy, Sanjoy (Dance Books Ltd., Alton,Hampshire (UK), 2004)
PALABRAS CLAVE: Slovenian company En-Knap, iztok kovac, S.K.I.N.
Dentro del apartado "Dance Now. Recent Reviews".